Battery diaphragm and manufacturing method thereof
By using the method of blending polymer particles and barium titanate in the lithium-ion battery separator, a multi-layer structure separator is formed by using the difference in density, the problems of poor heat resistance and high energy consumption during the preparation process are solved, and the problem of the existing separator is poor, which is achieved. High heat resistance and high adhesion, and reduces preparation costs.
Patent Information
- Application Number
- CN202411480801.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing lithium-ion battery separators have poor heat resistance, narrow heat pressing process window with the electrode sheet, high energy consumption during the preparation process, complex coating material formula and poor stability, resulting in coating properties parameters during the coating process Great fluctuations.
Using a battery separator structure including at least one base film, an inorganic layer and a plurality of polymer particles, the density of polymer particles is smaller than that of the inorganic layer, and the polymer particles are prepared by vegetable oils as raw materials to blend them with barium titanate. It is directly coated on the base film and dried, and the barium titanate is deposited and polymer particles are floating up by using the difference in density to form a separator with excellent heat resistance and high adhesion.
It realizes high heat resistance and high adhesion of the battery separator, reduces energy consumption and cost during the preparation process, adapts to the hot pressing process of different battery manufacturers, and maintains the hot pressing temperature range of 25 to 150°C and Adhesion of the pole sheet.
Smart Images

Figure CN119401064A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion battery separators, and in particular to a battery separator and a method for manufacturing the same. Background Art
[0002] The excessive use of fossil raw materials has led to serious environmental pollution problems. In view of the above problems, it is particularly important to use new energy materials to replace fossil raw materials. Lithium-ion batteries have been widely used in consumer electronics, power products and energy storage products due to their high energy density, high safety and stability, and long cycle life.
[0003] The battery separator is an important component in the lithium battery cell. At present, the battery separator with a microporous structure is usually prepared by extrusion, extraction and stretching of polyolefin materials. In order to improve the heat resistance of the separator, a polyolefin base film is usually coated with an inorganic material with high heat resistance (such as ceramics, cellulose, aramid, etc.). However, inorganic particles have poor dispersibility, are easy to fall off, and have serious powder loss. They need to be used with other components, which greatly increases the production cost. In addition, in order to meet the current battery preparation process requirements, it is necessary to ensure that there is strong adhesion between the separator and the pole piece to avoid misalignment of the pole ear. The current solution for producing a separator with high heat resistance and high adhesion is usually to coat an adhesive layer (PVDF) on the inorganic particle powder, but the softening point of PVDF is relatively high. When the hot pressing temperature is low, it is not easy to trigger the softening point of PVDF, so that the separator has no obvious adhesion with the positive and negative pole pieces.
[0004] The battery diaphragm proposed in the present invention can effectively solve the problems of poor heat resistance of existing battery diaphragms, narrow hot pressing process window between diaphragms and pole pieces, the current preparation of diaphragms with high heat resistance and high adhesion requires secondary coating, severe energy consumption, complex coating material formulation, and poor slurry stability resulting in large fluctuations in coating physical property parameters during the coating process. Compared with existing diaphragms, it has better performance. Summary of the invention
[0005] The object of the present invention is to provide a battery separator, characterized in that it includes: at least one base film; at least one inorganic layer located on the base film; a plurality of polymer particles, the plurality of polymer particles are located on the inorganic layer, and the density of the polymer particles is less than the density of the inorganic layer.
[0006] Preferably, the inorganic layer includes one or more of barium titanate, aluminum oxide, silicon dioxide and titanium dioxide.
[0007] Preferably, the polymer particles include one or more of a polyacrylonitrile layer, a polystyrene layer, a polyvinylidene fluoride layer, a polymethyl methacrylate layer, and a polyacrylamide layer.
[0008] Preferably, the polymer particles have a vegetable oil layer on the outside.
[0009] Preferably, the vegetable oil layer comprises one or more of sunflower seed oil, Chinese tallow tree oil, olive oil, rubber seed oil, castor oil, tung oil and palm oil.
[0010] Preferably, the polymer particles further include a plurality of cellulose nanofibrils, the plurality of cellulose nanofibrils are located outside the vegetable oil layer, and a portion of the plurality of cellulose nanofibrils are connected to the inorganic layer.
[0011] Preferably, the cellulose nanofibrils include one or more of cotton wool, paper pulp, wood pulp, and hemp.
[0012] Another object of the present invention is to provide a method for manufacturing a battery separator, which is characterized in that it includes: mixing vegetable oil, N-methylethanolamine, and a catalyst, and sealing and heating to obtain a vegetable oil-based precursor; mixing the vegetable oil-based precursor and anhydride, and sealing and heating to obtain a vegetable oil-based acrylate monomer; mixing the vegetable oil-based acrylate monomer, perbenzoic acid, and sodium carbonate, and sealing and stirring at room temperature to obtain a vegetable oil-based epoxy monomer; uniformly mixing the vegetable oil-based acrylate epoxy monomer, styrene monomer, methyl methacrylate monomer, vinylidene fluoride monomer, and acrylonitrile monomer, and then dropping them into a cellulose nanofibril suspension, mixing and stirring to obtain an oil-water mixture, and treating the oil-water mixture with an ultrasonic crusher to obtain a Pickering emulsion; dropping the Pickering emulsion into a mixed solvent of ethanol and water, adding a water-soluble initiator, cooling to room temperature after the reaction is completed, and then filtering with a filter to obtain a polymer composite emulsion; mixing the polymer composite emulsion with an inorganic substance to obtain a coating slurry; coating the coating slurry on a base film, and drying to obtain a battery separator.
[0013] Preferably, the cellulose nanofibril suspension comprises one or more of absorbent cotton, paper pulp, wood pulp and hemp.
[0014] Preferably, the inorganic substance includes one or more of barium titanate, aluminum oxide, silicon dioxide and titanium dioxide.
[0015] Preferably, the heating temperature after mixing the vegetable oil, the N-methylethanolamine and the catalyst is 50 to 80°C, and the reaction time is 8 hours; the heating temperature after mixing the vegetable oil-based precursor and the acid anhydride is 60 to 80°C, and the reaction time is 8 to 12 hours; the stirring time of the vegetable oil-based acrylate monomer, the perbenzoic acid and the sodium carbonate is 12 hours.
[0016] Preferably, it is characterized in that the processing power of the ultrasonic crusher is 600 to 800 watts, the processing time is 10 to 15 minutes, the Pickering emulsion is added dropwise to the mixed solvent and then the water-soluble initiator is added and polymerized at 60 to 80° C. for 2 to 4 hours.
[0017] Preferably, the oil-water ratio of the oil-water mixture is 1:4 to 8.
[0018] Preferably, the water-soluble initiator includes one or more of ammonium persulfate, potassium persulfate, and peroxide.
[0019] Preferably, after the coating slurry is coated on the base film, it is dried at 60 to 90° C. for 0.5 to 3 minutes.
[0020] This disclosure uses vegetable oil as raw material to synthesize vegetable oil-based acrylic ester monomers, and adds a certain proportion of methacrylate monomers, vinylidene fluoride monomers, acrylonitrile monomers, acrylamide monomers, and styrene monomers, using cellulose nanofibrils as stabilizers, a mixture of ethanol and water as dispersants, and azobisisobutyronitrile as initiators to perform dispersion polymerization. This preparation method is more environmentally friendly than the existing preparation method. After that, the prepared polymer particles with a multilayer structure are blended with barium titanate, and the blended slurry is directly coated on the base film and then placed in an oven for drying. During the drying process, there is a density difference between barium titanate and polymer particles, which causes the barium titanate with a higher density to sink and the polymer particles to float, so that the prepared battery separator has excellent heat resistance and high adhesion. And only one coating is required during the production process, and the energy and cost consumed can be greatly reduced compared to the currently commonly used secondary coating method. At the same time, the battery separator proposed by the present invention can be adapted to the hot pressing processes of different battery manufacturers, and has adhesion to the pole pieces at a hot pressing temperature between 25 and 150°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of a battery separator in one embodiment of the present invention.
[0022] Figure 2 FIG. 4 is a schematic diagram of polymer particles according to an embodiment of the present invention.
[0023] Figure 3 The present invention is a flowchart of a method for manufacturing a battery separator according to an embodiment of the present invention. DETAILED DESCRIPTION
[0024] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0025] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0026] Please refer to Figure 1 , Figure 1 Schematic diagram of a battery separator in one embodiment of the present invention. The battery separator 100 includes at least one base film 1, at least one inorganic layer 2 and a plurality of polymer particles 3. In one embodiment of the present invention, the polymer particles 3 are spherical. The inorganic layer 2 is located between the base film 1 and the plurality of polymer particles 3. The polymer particles 3 have a multilayer structure, and the density of the polymer particles 3 is less than the density of the inorganic layer 2. Preferably, the base film 1 can be made of polypropylene, and the inorganic layer 2 can include one or more of barium titanate, aluminum oxide, silicon dioxide, and titanium dioxide.
[0027] Please refer to Figure 2 , Figure 2 Schematic diagram of polymer particles in one embodiment of the present invention. The polymer particles 3 are high molecular polymers. The polymer particles 3 may include one or more of a polyacrylonitrile layer 31, a polystyrene layer 32, a polyvinylidene fluoride layer 33, a polymethyl methacrylate layer 34, and a polyacrylamide layer 35. In one embodiment of the present invention, the polymer particles 3 include, from the inside to the outside, a polyacrylonitrile layer 31, a polystyrene layer 32, a polyvinylidene fluoride layer 33, a polymethyl methacrylate layer 34, a polyacrylamide layer 35, a plant oil layer 36, and a plurality of cellulose nanofibrils 37. Preferably, the plant oil layer 36 may include one or more of sunflower seed oil, Chinese tallow tree oil, olive oil, rubber seed oil, castor oil, tung oil, and palm oil, and the cellulose nanofibrils may include one or more of absorbent cotton, pulp, wood pulp, and hemp.
[0028] Please refer to Figure 3 , Figure 3 The flowchart of the manufacturing method of the battery separator in one embodiment of the present invention is as follows.
[0029] In step S1, first prepare a vegetable oil-based acrylate epoxy monomer. Take 8 to 20 parts of vegetable oil, 1 to 4 parts of N-methylethanolamine, and 0.1 to 1 parts of a catalyst, mix them, seal and heat them to 50 to 80°C and react for 8 hours, then remove the unreacted substances and the catalyst to obtain a vegetable oil-based precursor. Mix 8 to 20 parts of a vegetable oil-based precursor and 2 to 15 parts of anhydride, seal and heat them to 60 to 80°C and react for 8 to 12 hours, then remove the unreacted substances to obtain a vegetable oil-based acrylate monomer. Then mix 8 to 20 parts of a vegetable oil-based acrylate monomer, 2 to 5 parts of perbenzoic acid, and 5 to 10 parts of sodium carbonate, seal and stir at room temperature for 12 hours, then remove the unreacted substances to obtain a vegetable oil-based acrylate epoxy monomer.
[0030] In step S2, a polymer composite emulsion and a coating slurry are prepared. 8 to 20 parts of vegetable oil-based acrylate epoxy monomer, 1 to 8 parts of styrene monomer, 1 to 3 parts of methyl methacrylate, 2 to 5 parts of vinylidene fluoride monomer, and 3 to 5 parts of acrylonitrile monomer are mixed and then added dropwise to 40 to 400 parts of cellulose nanofibril suspension. After stirring evenly, an oil-water mixture is obtained, and then treated with an ultrasonic crusher with a power of 600 to 800 watts for 10 to 15 minutes to obtain a Pickering emulsion. 60 to 80 parts of the Pickering emulsion are added dropwise to a mixed solvent of ethanol and water, and 0.2 to 0.4 parts of a water-soluble initiator are added. Preferably, the water-soluble initiator may include one or more of ammonium persulfate, potassium persulfate, and peroxide. The mixed solution is then placed in a constant temperature device and polymerized at 60 to 80° C. for 2 to 4 hours. After the reaction is completed, the temperature is lowered to room temperature and filtered with a 100 to 300 mesh nylon filter to obtain a polymer composite emulsion. Preferably, the oil-water ratio of the oil-water mixture is 1 to 4 to 8. Finally, 10 to 30 parts of the polymer composite emulsion are blended with 70 to 90 parts of barium titanate to obtain a coating slurry.
[0031] In another embodiment of the present invention, the formula ratio can be 0.1 to 2 parts of cellulose nanofibrils, 3 to 7 parts of vegetable oil polymers, 1 to 3 parts of polystyrene, 3 to 6 parts of polymethyl methacrylate, 1 to 5 parts of polyvinylidene fluoride, 1 to 3 parts of polyacrylonitrile, 1 to 4 parts of polyacrylamide, and 70 to 89.9 parts of barium titanate, with a total formula of 100 parts. In another embodiment of the present invention, the solid content of the cellulose nanofibrils is 0.1wt% to 1wt%.
[0032] In step S3, a battery separator is prepared by uniformly coating 1 to 3 portions of the coating slurry on the base film 1 by roller coating, and drying in a forced air oven at 60 to 90°C for 0.5 to 3 minutes. After drying, a battery separator having both heat resistance and adhesion is obtained.
[0033] The following examples are used to illustrate the method for preparing the battery separator in this disclosure.
[0034] Embodiment 1:
[0035] The preparation method of vegetable oil-based acrylate epoxy monomer specifically comprises the following steps:
[0036] (1) According to the mass fraction, 50 parts of palm oil were taken, purged with nitrogen at 100°C for 30 minutes, and then 8 parts of amino alcohol and 1 part of sodium methoxide solution (5 mol / L) were added to heat the palm oil to 65°C. After the reaction was sealed at 65°C for 8 hours, the mixture was poured into 50 parts of dichloromethane (DCM) to dissolve, and then washed with saturated sodium chloride and dried with anhydrous magnesium sulfate to obtain a vegetable oil-based precursor.
[0037] (2) 50 parts of a vegetable oil-based precursor, 15 parts of anhydride, and 0.4 parts of 4-dimethylaminopyridine were mixed, sealed and heated to 65°C for reaction for 8 hours, then poured into 50 parts of dichloromethane for dissolution, washed with saturated sodium bicarbonate and saturated sodium chloride, respectively, and then dried with anhydrous magnesium sulfate and then passed through an alkaline alumina column to obtain a vegetable oil-based acrylate monomer.
[0038] (3) 50 parts of vegetable oil-based monomer, 10 parts of sodium carbonate and 6 parts of hydrogen peroxide were added dropwise to 50 parts of dichloromethane to dissolve, stirred at room temperature for 8 hours, washed with saturated sodium thiosulfate, saturated sodium bicarbonate and saturated sodium chloride solutions, dried with anhydrous magnesium sulfate and then passed through an alkaline alumina column to obtain a vegetable oil-based acrylate epoxy monomer.
[0039] Embodiment 2:
[0040] The preparation method of the battery separator specifically comprises the following steps:
[0041] (1) According to the weight percentage, 5 parts of the vegetable oil-based acrylate epoxy monomer prepared in Example 1, 2 parts of styrene monomer, 4 parts of methyl methacrylate, 3 parts of vinylidene fluoride, 2 parts of acrylonitrile, and 4 parts of acrylamide monomer were mixed and then added dropwise to 80 parts of 0.2wt% cellulose nanofibril suspension, and after being fully mixed, the mixture was treated with an ultrasonic crusher with a power of 600 watts for 10 minutes to obtain Pickering emulsion 1. The stability, particle size and viscosity parameters of Pickering emulsion 1 are shown in Table 1.
[0042] (2) 50 parts of Pickering emulsion 1 were placed in a thermostatic device at 65°C and deoxygenated with nitrogen for 30 minutes, and then 0.2 parts of a water-soluble initiator potassium persulfate were added to react for 3 hours. The temperature was then raised to 80°C and reacted for 30 minutes. The temperature was then lowered to room temperature and filtered with a 100-mesh nylon filter to obtain a polymer composite emulsion.
[0043] (3) 10 parts of the polymer composite emulsion and 90 parts of the barium titanate solution (solid content 20 wt%) were mixed and mechanically stirred for 2 hours to obtain a coating slurry, which was then evenly coated on a polypropylene base film using a roller coater and dried in an oven at 60°C for 1 minute to obtain a battery separator.
[0044] Comparative Example 1:
[0045] The preparation method of the battery separator specifically comprises the following steps:
[0046] (1) According to the weight percentage, 5 parts of the vegetable oil-based acrylate epoxy monomer prepared in Example 1, 2 parts of styrene monomer, 4 parts of methyl methacrylate, 3 parts of vinylidene fluoride, 2 parts of acrylonitrile, and 4 parts of acrylamide monomer were mixed and then added dropwise to 80 parts of 0.5wt% cellulose nanofibril suspension, and after being fully mixed, the mixture was treated with an ultrasonic crusher with a power of 600 watts for 10 minutes to obtain Pickering emulsion 2. The stability, particle size and viscosity parameters of Pickering emulsion 2 are shown in Table 1.
[0047] (2) 50 parts of Pickering emulsion 2 were placed in a thermostatic device at 65°C and deoxygenated with nitrogen for 30 minutes, and then 0.2 parts of a water-soluble initiator potassium persulfate were added to react for 3 hours. The temperature was then raised to 80°C and reacted for 30 minutes before being cooled to room temperature. The mixture was then filtered through a 100-mesh nylon filter to obtain a polymer composite emulsion.
[0048] (3) 10 parts of the polymer composite emulsion and 90 parts of the barium titanate solution (solid content 20 wt%) were mixed and mechanically stirred for 2 hours to obtain a coating slurry, which was then evenly coated on a polypropylene base film using a roller coater and dried in an oven at 60°C for 1 minute to obtain a battery separator.
[0049] Comparative Example 2:
[0050] The preparation method of the battery separator specifically comprises the following steps:
[0051] (1) According to the weight percentage, 5 parts of the vegetable oil-based acrylate epoxy monomer prepared in Example 1, 2 parts of styrene monomer, 4 parts of methyl methacrylate, 3 parts of vinylidene fluoride, 2 parts of acrylonitrile, and 4 parts of acrylamide monomer were mixed and then added dropwise to 160 parts of a 0.2wt% cellulose nanofibril suspension, and after being fully mixed, the mixture was treated with an ultrasonic crusher with a power of 600 watts for 10 minutes to obtain Pickering emulsion 3. The stability, particle size and viscosity parameters of Pickering emulsion 3 are shown in Table 1.
[0052] (2) 50 parts of Pickering emulsion 3 were placed in a thermostatic device at 65°C and deoxygenated with nitrogen for 30 minutes. Then 0.2 parts of a water-soluble initiator, potassium persulfate, were added to react for 3 hours. The temperature was then raised to 80°C and reacted for 30 minutes. The temperature was then lowered to room temperature and filtered through a 100-mesh nylon filter to obtain a polymer composite emulsion.
[0053] (3) 10 parts of the polymer composite emulsion and 90 parts of the barium titanate solution (solid content 20 wt%) were mixed and mechanically stirred for 2 hours to obtain a coating slurry, which was then evenly coated on a polypropylene base film using a roller coater and dried in an oven at 60°C for 1 minute to obtain a battery separator.
[0054] Comparative Example 3:
[0055] The preparation method of the battery separator specifically comprises the following steps:
[0056] (1) According to the weight percentage, 5 parts of the vegetable oil-based acrylate epoxy monomer prepared in Example 1, 2 parts of styrene monomer, 4 parts of methyl methacrylate, 3 parts of vinylidene fluoride, 2 parts of acrylonitrile, and 4 parts of acrylamide monomer were mixed and added dropwise to 80 parts of 0.2 wt% cellulose nanofibril suspension. After being fully mixed, the mixture was treated with an ultrasonic crusher with a power of 600 watts for 10 minutes to obtain Pickering emulsion 1.
[0057] (2) 50 parts of Pickering emulsion 1 were placed in a thermostatic device at 65°C and deoxygenated with nitrogen for 30 minutes, and then 0.2 parts of a water-soluble initiator potassium persulfate were added to react for 3 hours. The temperature was then raised to 80°C and reacted for 30 minutes before being cooled to room temperature. The mixture was then filtered through a 100-mesh nylon filter to obtain a polymer composite emulsion.
[0058] (3) Take 10 parts of the polymer composite emulsion and evenly coat it on a polypropylene base film with a roller coater, and dry it in an oven at 60° C. for 1 minute to obtain a battery separator.
[0059] Table 1
[0060]
[0061]
[0062] The characteristic parameters of the battery separators prepared in Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are shown in Table 2. It can be seen from Table 2 that the battery separator prepared in Example 2 has the smallest thermal shrinkage rate and the largest positive electrode bonding strength.
[0063] Table 2
[0064]
[0065] This disclosure uses vegetable oil as raw material to synthesize vegetable oil-based acrylic ester monomers, and adds a certain proportion of methacrylate monomers, vinylidene fluoride monomers, acrylonitrile monomers, acrylamide monomers, and styrene monomers, using cellulose nanofibrils as stabilizers, a mixture of ethanol and water as dispersants, and azobisisobutyronitrile as initiators to perform dispersion polymerization. This preparation method is more environmentally friendly than the existing preparation method. After that, the prepared polymer particles with a multilayer structure are blended with barium titanate, and the blended slurry is directly coated on the base film and then placed in an oven for drying. During the drying process, there is a density difference between barium titanate and polymer particles, which causes the barium titanate with a higher density to sink and the polymer particles to float, so that the prepared battery separator has excellent heat resistance and high adhesion. And only one coating is required during the production process, and the energy and cost consumed can be greatly reduced compared to the currently commonly used secondary coating method. At the same time, the battery separator proposed by the present invention can be adapted to the hot pressing processes of different battery manufacturers, and has adhesion to the pole pieces at a hot pressing temperature between 25 and 150°C.
[0066] The above descriptions are only some specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A battery separator, characterized in that: include: at least one basement membrane; At least one inorganic layer, located on the base film; A plurality of polymer particles are disposed on the inorganic layer, and the density of the polymer particles is lower than that of the inorganic layer.
2. The battery separator according to claim 1, characterized in that: The inorganic layer includes one or more of barium titanate, aluminum oxide, silicon dioxide, and titanium dioxide.
3. The battery separator according to claim 2, characterized in that: The polymer particles include one or more of a polyacrylonitrile layer, a polystyrene layer, a polyvinylidene fluoride layer, a polymethyl methacrylate layer, and a polyacrylamide layer.
4. The battery separator according to claim 3, characterized in that: The outer side of the polymer particles is provided with a vegetable oil layer.
5. The battery separator according to claim 4, characterized in that: The vegetable oil layer includes one or more of sunflower seed oil, Chinese tallow tree oil, olive oil, rubber seed oil, castor oil, tung oil and palm oil.
6. The battery separator according to claim 4, characterized in that: The polymer particles further include a plurality of cellulose nanofibrils, the plurality of cellulose nanofibrils are located outside the vegetable oil layer, and a portion of the plurality of cellulose nanofibrils is connected to the inorganic layer.
7. The battery separator according to claim 6, characterized in that: The cellulose nanofibrils include one or more of absorbent cotton, paper pulp, wood pulp, and hemp.
8. A method for manufacturing a battery separator, characterized in that: include: The vegetable oil, N-methylethanolamine and a catalyst are mixed, sealed and heated to obtain a vegetable oil-based precursor; The plant oil-based precursor and the acid anhydride are mixed, sealed and heated to obtain a plant oil-based acrylate monomer; The vegetable oil-based acrylate monomer, perbenzoic acid and sodium carbonate are mixed, sealed and stirred at room temperature to obtain a vegetable oil-based epoxy monomer; The plant oil-based acrylate epoxy monomer, styrene monomer, methyl methacrylate monomer, vinylidene fluoride monomer, and acrylonitrile monomer are uniformly mixed and then added dropwise to the cellulose nanofibril suspension, and an oil-water mixture is obtained after mixing and stirring, and the oil-water mixture is treated with an ultrasonic crusher to obtain a Pickering emulsion; The Pickering emulsion is added dropwise to a mixed solvent of ethanol and water, a water-soluble initiator is added, the temperature is cooled to room temperature after the reaction is completed, and then filtered with a filter to obtain a polymer composite emulsion; Mixing the polymer composite emulsion with an inorganic substance to obtain a coating slurry; The coating slurry is coated on a base film and dried to obtain a battery separator.
9. The method for manufacturing a battery separator according to claim 8, characterized in that: The cellulose nanofibril suspension includes one or more of absorbent cotton, paper pulp, wood pulp and hemp.
10. The method for manufacturing a battery separator according to claim 8, characterized in that: The inorganic substance includes one or more of barium titanate, aluminum oxide, silicon dioxide and titanium dioxide.
11. The method for manufacturing a battery separator according to claim 8, characterized in that: The heating temperature after mixing the vegetable oil, the N-methylethanolamine and the catalyst is 50 to 80° C., and the reaction time is 8 hours. The heating temperature after mixing the vegetable oil-based precursor and the acid anhydride is 60 to 80° C., and the reaction time is 8 to 12 hours. The stirring time of mixing the vegetable oil-based acrylate monomer, the perbenzoic acid and the sodium carbonate is 12 hours.
12. The method for manufacturing a battery separator according to claim 11, characterized in that: The processing power of the ultrasonic crusher is 600 to 800 watts, and the processing time is 10 to 15 minutes. The Pickering emulsion is added dropwise to the mixed solvent and then the water-soluble initiator is added to polymerize at 60 to 80° C. for 2 to 4 hours.
13. The method for manufacturing a battery separator according to claim 8, characterized in that: The oil-water ratio of the oil-water mixture is 1:4 to 8.
14. The method for manufacturing a battery separator according to claim 8, characterized in that: The water-soluble initiator includes one or more of ammonium persulfate, potassium persulfate, and peroxide.
15. The method for manufacturing a battery separator according to claim 12, characterized in that: The coating slurry is coated on the base film and then dried at 60 to 90° C. for 0.5 to 3 minutes.
Citation Information
Patent Citations
Isolating membrane for lithium ion secondary battery
CN104953070A
Lithium-ion battery diaphragm suitable or hot dry pressing and preparation method thereof
CN106898721A
Graft modified ceramic particle, lithium ion battery diaphragm, lithium ion battery and battery module
CN112194410A
Composite diaphragm coating, modified diaphragm as well as preparation method and application of modified diaphragm
CN117937054A
Method for preparing lithium battery diaphragm by utilizing Pickering emulsion polymerization
CN118165183A
Cited By
Lithium ion battery diaphragm and preparation method thereof
CN119627369A